PENGARUH TOTALITAS GURU PPKN TERHADAP NILAI PPKN SISWA SMK AL-KHAIRIYAH CIOMAS KABUPATEN SERANG - Herawati, Herawati (UNTIRTA CIVIC EDUCATION JOURNAL, 2022)
This study aims to determine the effect of the totality of teachers on the PPKn value of students at SMK Al-Khairiyah Ciomas Serang Regency. The formulation of the problem in this research is how the influence of totality of teachers on the value of PPKn Students at SMK Al-Khairiyah Ciomas Serang Regency The method used in this study is to use a quantitative survey method using statistical data calculations with several tests, namely validity test, reliability test, correlation test , normality test, determination test and hypothesis testing. The sample in this study was 119 samples. While the results obtained in this study is that the totality of teachers in teaching and learning activities at SMK Al-Khairiyah Ciomas Serang Regency is categorized as very good. This is based on the results of data processing, it can be obtained that 4.44 numbers are in the 4.25-4.44 area. While the results of the correlation data acquisition is 0.017